Experimental analysis of particulate movement in a large Eddy Simulation Chamber - Padilla, Angelina Marianna (Kansas State University, 2008)
Millions of people travel by commercial aircraft each year. The close proximity of passengers aboard an airplane leads to one of the primary reasons that air quality in an aircraft cabin is of interest. In recent years there have been multiple reported instances of people contracting illnesses after being aboard an aircraft for an extended period of time. In order to better understand air quality in an aircraft cabin, an experimental study of particulate transport in a half cabin model of a Boeing 767 was performed. In the study, both 3[Mu]m and 10[Mu]m particles were tested separately by injecting them into the cabin through a vertical tube, 609.6 mm (24 in) above the floor, at a single location on the centerline of the half cabin test section. Resulting particulate concentrations were measured at five locations along the centerline of the half cabin test section. It was found that for the 3[Mu]m particles, the normalized concentration was about one for all of the locations except directly above the injection site. Therefore, the concentrations were approximately the same as the well-mixed concentration, where the well-mixed concentration is the concentration in the test cabin if the test cabin is uniformly mixed. For the same test conditions, the normalized concentrations for the 10[Mu]m particles were well below one, around 0.1. Several more concentration measurements using the 10[Mu]m particles were taken at the same five locations, both on and off the centerline, and for different particle injection and cabin pressure conditions. The concentration results using a diffuser cone to inject the 10[Mu]m particles into the test cabin and a neutral cabin pressure were higher than the results found using the straight injection tube, but they were not very repeatable. After pressurizing the cabin to slightly above ambient pressure and using the diffuser cone, the resulting average normalized particle concentrations along the centerline were found to be between 0.4 and 1.5 and repeatable within the estimated measurement uncertainty. Therefore, it appears that the 3[Mu]m particles follow the airflow in the test cabin well, but it is not clear if the 10[Mu]m particles do as well.
Keywords: Particle transport; Indoor particulate movement; Ventinlated chamber; Engineering, Aerospace (0538); Engineering, Environmental (0775)